Safe care mobile application for surgical patients: development, content validation, and usability validation - Liliane de Lourdes Teixeira Silva; Rafael Corbelli de Lima; Rone Ilideo da Silva; Vanessa de Brito Poveda (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To describe the development, content validation, and usability of an application to orient surgical patients and ensure their safety. Method: Methodological study, carried out between July and August 2023, developed in three stages: (1) selection of relevant content based on a review of scientific literature; (2) development of the application; and (3) validation of the content and usability of the software, evaluated using two validated instruments, which were sent to eight nurse judges from the states of São Paulo, Minas Gerais, and Santa Catarina, and eight professional information technology judges from Minas Gerais. Results: The contents of the "Minha Cirurgia" application included information based on relevant scientific literature regarding patient safety, preoperative guidelines, timing of surgery, and post-surgical care. Its content was classified as "superior" and its usability was classified as "the best possible" by the judges. Conclusion: The application was approved by nurses and IT professionals regarding its content and usability. It will be available for free download in the Play Store. The tool is expected to be useful in the education of surgical patients, allowing them to acquire knowledge that supports them in the search for safe care.